Loss, dying and bereavement in the criminal justice system - Read, Sue (Routledge key themes in health and society, 2018)
Introduction: collective responsibilities for compassionate support / Sue Read, Sotirios Santatzoglou & Anthony Wrigley -- Appreciating dimensions of loss, death, dying and bereavement -- Disenfranchised communities / Sue Read -- Death, dying and maintaining hope : ethical tensions and responsibilities in the prison setting / Anthony Wrigley -- "Sympathy to the offender" : the hobbesian account and the sympathy to the offender as an issue in end of life care -- Loss at the end of life : palliative care in prisons / Kate Lillie -- Deaths in sites of state confinement : a continuum of routine violence and terror / Bree Carlton, Joe Sim and Steve Tombs -- Civil and social death : criminalisation and the loss of the self / Andrew Henley -- Áprofessional development of bereavement and end of life practice -- Bereavement and loss at the sentencing stage / Martin Wasik -- Criminal justice context and voluntary bereavement support / Mary S Corcoran -- "Sympathy to the offender" : the hobbesian account and the sympathy to the offender as an issue in end of life care part b / Sue Read, Sotirios Santatzoglou -- Working in the shadows : reflections on counselling in prison and hospice settings / Alison Soulsby -- The evolution of change : factors involved in the design and delivery of a therapeutic service within the confines of a custodial setting / David Pitt, Lisa Thomson -- Offenders and the challenges of palliative care in the community setting. steve cartwright -- Insights to inform reflections for ongoing support -- Sorrow, loss and the transition of chronic disease to end of life careáin prisons / Sue Ashby -- The impact of loss on mental health: implications for practice / Alexis Warrilow -- Mourning in custody : dealing with sudden death / Jane Jervis -- Freedom to grieve: a child and parent perspective / Gill Clifford, Kevin Benson -- Beyond loss of liberty : how loss, bereavement and grief can affect young men's prison journeys / Nina Vaswani -- Grief, chaplaincy and the non-religious prisoner / Katie Hunt, Sue Read